Impact of Pharmacist-Led Interventions on Diabetes Management at a Community Pharmacy in Pakistan: A Randomized Controlled Trial - Muhammad Abubakar MPhil; Muhammad Atif PhD (SAGE Publishing, 2021)
Purpose The study aimed to determine the impact of pharmacist-led interventions on diabetes management at a community pharmacy in Pakistan. Methods A one-month follow-up, randomized controlled trial (RCT) was carried out between December 1, 2016 and June 30, 2017. Sampling population consisted of patients diagnosed with type 2 diabetes mellitus (T2DM). The study population was randomized to a control group or an intervention group to determine the impact of a community pharmacist intervention on glycemic control fasting blood glucose (FBG) and random blood glucose (RBG), medication adherence (MMAS), and health-related quality of life (HRQoL) (EQ-5D-3L). Both non-pharmacological and pharmacological interventional tools were used that consist of array of charts and verbal communication by pharmacist. Outcomes for continuous variables were analyzed using paired sample t-test for time effect and one sample t-test to evaluate the study group effect. Independent sample t-test was used to compare each independent variable with dependent variable. A P -value of <.05 was considered statistically significant. Results The control and intervention groups showed significant improvement ( P -value < .05) in glycemic control, medication adherence, and HRQoL. However, the difference between the control and intervention groups was not statistically significant in terms of blood glucose levels and HRQoL (time trade off, TTO). There was a clinically significant association between pharmacist intervention and predefined glycemic control among the study participants (FBG: P -value < .001 and RBG: P -value = .04). A clinically significant association was also found between pharmacist intervention and medication adherence at the end of the trial compared with baseline values ( P -value < .001). Similarly, a clinically significant association was found between pharmacist intervention and predefined HRQoL [TTO: P -value = .002 and EQ-VAS: P -value = .001]. Conclusion A significant proportion of T2DM patients in the intervention group achieved predefined glycemic control, medication adherence, and health related quality of life.